Biopsy Proven Renal Diseases:Clinicopathological Correlations - Sohail Sabir (Journal of Rawalpindi Medical College, 2013)
Background: To determine the clinicopathological correlations of biopsy proven renal disease (BPRD). Methods: In this descriptive study all the consecutive percutaneous renal biopsies (RB) were included in the study. The indications for RB were classified into the five clinical categories, i,e, nephrotic syndrome (NS), non-nephrotic proteinuria (NNP), proteinuria-hematuria (PH), renal failure (RF), and rapidly progressive glomerulonephritis (RPGN). All the biopsies were obtained by percutaneous automated biopsy gun under ultrasonographic guidance.The histopathological study included light microscopy (LM) and immunofluorescence (IF). For LM, 3 sections were stained with Hematoxylin and Eosin (H&E), two with periodic acid Schiff (PAS), one with Masson’s trichrome, and one with Jones silver methanamine (JMS). IF study was done by using polyclonal antibodies against human IgG, IgM, IgA, C3, and C1q. Results: A total 47 cases met the inclusion criteria of the study. The mean age was 33.23±12.11 years. Nephrotic syndrome (NS) (55.31%) was the most frequent indication. Focal segmental glomerulosclerosis (FSGS) was the most common cause of NS(42.3%),followed by membranous GN (MN) (26.9%), while chronic sclerosing GN was the most common cause of RF. The mean total number of glomeruli included in all RBs was 14.43±7.06. The mean number of globally sclerosed glomeruli was 3.66±6.23 (range: 0-39) and the mean of segmentally sclerosed glomeruli, 0.94±1.55 (range: 0-7). Overall, global glomerulosclerosis (GS) was found in 66% biopsies, and segmental glomerulosclerosis (SS) in 19 (40.4%) biopsies. Arteriolosclerosis (AS) was present in 25.5% of biopsies and hyaline arteriolosclerosis in 23.4%. Fibrointimal thickening of arteries was found in 27.6% cases. A variable degree of interstitial fibrosis and tubular atrophy (IFTA) was found in 87.2% and interstitial inflammation in 34%. Acute tubular necrosis (ATN) was found in 10.6%. Conclusion: Nephrotic syndrome was the commonest indication for performing renal biopsy and focal segmental glomerulosclerosis was the commonest cause of nephritic syndrome..